The digital commercialisation of US politics — 2020 and beyond - Jeff Chester; Kathryn C. Montgomery (Internet Policy Review, 2019)
The same micro-targeted programmatic advertising that has become central to the digital media and marketing ecosystem has now migrated into election campaigns in the US and elsewhere, raising a host of issues around privacy, discrimination, and manipulation. This paper examines the digital strategies and technologies of today's political campaigns, explaining how they will be deployed in the upcoming 2020 election cycle, and assessing regulatory and policy responses — both enacted and proposed — for increasing transparency and accountability in digital politics.
Keywords: 300; Advertising; Elections; Micro-targeting; Privacy